SOME NOTES ON IFRS CONVERGENCE AND THE ISLAMIC FINANCIAL INDUSTRY - Ratna Mulyany (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2018)
IFRS Convergence has been a worldwide phenomenon with most of countries in the world are adoptingIFRS instead of their national accounting standards. At the same time, the Islamic finance is gaining its popularity in the present world with the increasing acceptance by international community. In relation to these two phenomena, there have been concerns that the establishment of Islamic financial institutions together with its own unique characteristics will impede the achievement of the global accounting convergence. Furthermore, the promulgation of accounting standards by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), which is intended to fulfil the unique features of Islamic Financial Industry is viewed as a challenge to the International Financial Reporting Standards (IFRS), which is promoted by the convergence agenda. Numerous complex issues emerge as result of the dilemmatic position of IFIs in retaining its distinct Shari’ah principles, while attempting to be part of the global financial system through adopting the IFRS. This study aims to describe some notes relating to the IFRS convergence and the development of Islamic finance. The objective is to outline the issues, not necessarily to resolve them, and to consider the implications they have for pursuing IFRS convergence in the context of Islamic financial service industry.